2013
DOI: 10.1101/lm.029504.112
|View full text |Cite
|
Sign up to set email alerts
|

Traces of memory: Reacquisition of fear following forgetting is NMDAr-independent

Abstract: Recent research shows that while initial learning is dependent on N-methyl-D-aspartate receptors (NMDArs), relearning can be NMDAr-independent. In the present study we examined whether this switch also occurs following forgetting. The developing animal exhibits much more rapid rates of forgetting than adults, so infant rats were used. It was found that infant rats required NMDArs to learn fear (Experiment 1), and that this memory was forgotten after 14 d (Experiment 2). Despite forgetting, relearning fear did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 50 publications
3
35
2
Order By: Relevance
“…Traditionally, developmental stages in the rodent were based upon the timing of key structural events such as the brain growth spurt [39,40], but in the context of learning and memory we believe it is more appropriate to align developmental stages with the emergence of specific cognitive functions. Rodents up to P23 have been referred to as 'infants' in previous studies, presumably referring to a range of immaturity other than adolescence [41][42][43][44][45]. However, findings accumulating from the last few decades suggest that the cut-off for the end of infancy should be much earlier than this.…”
Section: Developmental Stages In Humans and Rodentsmentioning
confidence: 93%
See 1 more Smart Citation
“…Traditionally, developmental stages in the rodent were based upon the timing of key structural events such as the brain growth spurt [39,40], but in the context of learning and memory we believe it is more appropriate to align developmental stages with the emergence of specific cognitive functions. Rodents up to P23 have been referred to as 'infants' in previous studies, presumably referring to a range of immaturity other than adolescence [41][42][43][44][45]. However, findings accumulating from the last few decades suggest that the cut-off for the end of infancy should be much earlier than this.…”
Section: Developmental Stages In Humans and Rodentsmentioning
confidence: 93%
“…Further evidence for the existence of a memory trace was provided by Richardson and colleagues, who elegantly demonstrated that fear conditioning during infancy, though rapidly forgotten, impacts the neurobiology of later learning [44]. This work is based on how the acquisition of initial fear learning activates a complex intracellular signalling cascade involving glutamate release, activation of protein kinases (such as MAPK) and protein synthesis [23], and disruption of any part of this pathway can interfere with initial learning.…”
Section: In Search Of the Engram: Discovery Of A Neural Trace Of A Fomentioning
confidence: 97%
“…The idea that an unexpressed memory trace might have an "implicit" effect on later performance in rodents was recently explored by Li and Richardson (2013). In that study, the effect of a memory acquired during infancy, but then forgotten, on the neurobiological mechanisms mediating future learning experiences was examined.…”
Section: Implicit Versus Explicit Memorymentioning
confidence: 99%
“…This is referred to as a "switch" from NMDAr-dependent acquisition to NMDAr-independent reacquisition. Li and Richardson (2013) explored whether this switch to NMDAr-independent reacquisition still occurred if the original learning had been forgotten. Infant rats were trained at 17 d of age with noise CS-shock US pairings.…”
Section: Implicit Versus Explicit Memorymentioning
confidence: 99%
See 1 more Smart Citation